Protein therapy of skeletal muscle atrophy and mechanism by angiogenic factor AGGF1. Issue 2 (25th January 2023) - He, Zuhan; Song, Qixue; Yu, Yubing; Liu, Feng; Zhao, Jinyan; Un, Waikeong; Da, Xingwen; Xu, Chengqi; Yao, Yufeng; Wang, Qing K.
Abstract: Background: Skeletal muscle atrophy is a common condition without a pharmacologic therapy. AGGF1 encodes an angiogenic factor that regulates cell differentiation, proliferation, migration, apoptosis, autophagy and endoplasmic reticulum stress, promotes vasculogenesis and angiogenesis and successfully treats cardiovascular diseases. Here, we report the important role of AGGF1 in the pathogenesis of skeletal muscle atrophy and attenuation of muscle atrophy by AGGF1. Methods: In vivo studies were carried out in impaired leg muscles from patients with lumbar disc herniation, two mouse models for skeletal muscle atrophy (denervation and cancer cachexia) and heterozygous Aggf1 +/− mice. Mouse muscle atrophy phenotypes were characterized by body weight and myotube cross‐sectional areas (CSA) using H&E staining and immunostaining for dystrophin. Molecular mechanistic studies include co‐immunoprecipitation (Co‐IP), western blotting, quantitative real‐time PCR analysis and immunostaining analysis. Results: Heterozygous Aggf1 +/− mice showed exacerbated phenotypes of reduced muscle mass, myotube CSA, MyHC (myosin heavy chain) and α‐actin, increased inflammation (macrophage infiltration), apoptosis and fibrosis after denervation and cachexia. Intramuscular and intraperitoneal injection of recombinant AGGF1 protein attenuates atrophy phenotypes in mice with denervation (gastrocnemius weight 81.3 ± 5.7 mg vs. 67.3 ± 5.1 mg for AGGF1 vs. buffer; P  < 0.05) and cachexia (133.7 ± 4.7 vs. 124.3 ± 3.2; P  < 0.05). AGGF1 expression undergoes remodelling and is up‐regulated in gastrocnemius and soleus muscles from atrophy mice and impaired leg muscles from patients with lumbar disc herniation by 50–60% ( P  < 0.01). Mechanistically, AGGF1 interacts with TWEAK (tumour necrosis factor‐like weak inducer of apoptosis), which reduces interaction between TWEAK and its receptor Fn14 (fibroblast growth factor‐inducing protein 14). This leads to inhibition of Fn14‐induced NF‐kappa B (NF‐κB) p65 phosphorylation, which reduces expression of muscle‐specific E3 ubiquitin ligase MuRF1 (muscle RING finger 1), resulting in increased MyHC and α‐actin and partial reversal of atrophy phenotypes. Autophagy is reduced in Aggf1 +/− mice due to inhibition of JNK (c‐Jun N‐terminal kinase) activation in denervated and cachectic muscles, and AGGF1 treatment enhances autophagy in two atrophy models by activating JNK. In impaired leg muscles of patients with lumbar disc herniation, MuRF1 is up‐regulated and MyHC and α‐actin are down‐regulated; these effects are reversed by AGGF1 by 50% ( P  < 0.01). Conclusions: These results indicate that AGGF1 is a novel regulator for the pathogenesis of skeletal muscle atrophy and attenuates skeletal muscle atrophy by promoting autophagy and inhibiting MuRF1 expression through a molecular signalling pathway of AGGF1‐TWEAK/Fn14‐NF‐κB. More importantly, the results indicate that AGGF1 protein therapy may be a novel approach to treat patients with skeletal muscle atrophy.